2018
DOI: 10.1177/0954407018804118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of injection strategies on knock resistance and combustion characteristics in a DISI engine

Abstract: The combustion of a direct injection spark ignition engine is significantly affected by the fuel injection strategy due to the impact this strategy has on the gas-mixture formation and the turbulence flow. However, comprehensive assessments on both knock and engine performances for different injection strategies are generally lacking. Therefore, the main objective of the present study is to provide an experimental evidence of how a single injection strategy and a split injection strategy compare in terms of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Nevertheless, several studies [5][6][7] forecast that internal combustion engines (ICEs) will continue to play an important role among vehicular propulsion systems for the next decade (also foreseeing their application in hybrid powertrains or thanks to the use of synthetic fuels) and for distributed energy generation solutions. In this context, gasoline direct injection (DI) in spark ignition (SI) engines has been widely adopted in recent years, often in combination with engine downsizing and turbocharging, due to its capability to significantly reduce knock tendency [8][9][10]. The possibility of implementing lean burn combustion systems and reducing fuel consumption is a further advantage of DISI engines [11][12][13], even if this operating regime requires specific aftertreatment systems [14] and features lower combustion stability [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several studies [5][6][7] forecast that internal combustion engines (ICEs) will continue to play an important role among vehicular propulsion systems for the next decade (also foreseeing their application in hybrid powertrains or thanks to the use of synthetic fuels) and for distributed energy generation solutions. In this context, gasoline direct injection (DI) in spark ignition (SI) engines has been widely adopted in recent years, often in combination with engine downsizing and turbocharging, due to its capability to significantly reduce knock tendency [8][9][10]. The possibility of implementing lean burn combustion systems and reducing fuel consumption is a further advantage of DISI engines [11][12][13], even if this operating regime requires specific aftertreatment systems [14] and features lower combustion stability [15].…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Recent research indicated that compared to single injection (SI), split injection could expand the knock limit and increase the indicated thermal efficiency through charge cooling effect and advancing combustion phase. [ 17,18 ] LBC and high compression ratio (CR) are the two main technologies to improve thermal efficiency [ 19–21 ] but the fact that the CR of spark ignition engine is constrained by the knock combustion. Ning et al [ 20 ] investigated the LBC characteristics in a high CR DISI methanol engine and discovered that under λ = 1.4, greater brake thermal efficiency was obtained.…”
Section: Introductionmentioning
confidence: 99%